2008
DOI: 10.1021/ie801316d
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Moment Sets for Multivariate Direct Quadrature Method of Moments

Abstract: The direct quadrature method of moments (DQMOM) can be employed to close population balance equations (PBEs) governing a wide class of multivariate number density functions (NDFs). Such equations occur over a vast range of scientific applications, including aerosol science, kinetic theory, multiphase flows, turbulence modeling, and control theory, to name just a few. As the name implies, DQMOM uses quadrature weights and abscissas to approximate the moments of the NDF, and the number of quadrature nodes determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 40 publications
0
38
0
Order By: Relevance
“…However, for some cases (e.g., infinite Knudsen number with walls at different temperatures), the tensor product formulation can be overly restrictive, leading to negative weights. In order to overcome this shortcoming, we have recently developed less restrictive moment-inversion algorithms using conditional moments [39] based on the "optimal" moments sets reported in [20], for which non-negative weights are guaranteed for any optimal set of realizable moments. Results using this conditional quadrature method of moments (CQMOM) will be reported elsewhere.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for some cases (e.g., infinite Knudsen number with walls at different temperatures), the tensor product formulation can be overly restrictive, leading to negative weights. In order to overcome this shortcoming, we have recently developed less restrictive moment-inversion algorithms using conditional moments [39] based on the "optimal" moments sets reported in [20], for which non-negative weights are guaranteed for any optimal set of realizable moments. Results using this conditional quadrature method of moments (CQMOM) will be reported elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…Once the fluxes G w,in and G w,out are known, the temporary quadrature weights at the wall are rescaled to satisfy the continuity constraint: 20) and the moments are recomputed from (3.3) using the updated set of weights and abscissas. Note that this procedure is equivalent to representing the equilibrium wall distribution function by…”
Section: Quadrature-based Boundary Conditions For the Momentsmentioning
confidence: 99%
“…In the direct quadrature method of moments (DQMOM) the population balance is converted into a set of ordinary differential equations for selected moments (Fox, 2009;Marchisio and Fox, 2005;Marchisio et al, 2003a). …”
Section: Dqmommentioning
confidence: 99%
“…Its chief disadvantage is that it is not well-suited for systems that involve space and time gradients. (iii) Direct quadrature method of moments (DQMOM): this methodology is very efficient in one-component systems and is currently the only viable option for interfacing the PBE with fluid dynamics (Fox, 2009;Marchisio and Fox, 2005;Marchisio et al, 2003b;Marchisio et al, 2003c). Extension to two-component systems is not straightforward and requires validation against known solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Direct quadrature method of moments is an efficient technique for singlecomponent coagulation simulations. 8,9 However, Marshal et al showed this method is not as accurate as cNMC simulation for bicomponent coagulation processes.10 Yu et al employed Taylor expansions to derive a closed finite dimensional ODE system that models a single-component coagulation process.11 The accuracy of the system improves with increasing the Taylor expansion's order, which is equal to the number of moments considered in the model. In this manuscript, we exploit the idea in Yu et al's work but for bicomponent coagulation processes.…”
mentioning
confidence: 99%